ANALISIS PENGARUH MANAJEMEN LEMBAGA PENDIDIKAN DAN PELATIHAN NON FORMAL (LPPNF) TERHADAP SUMBER DAYA MANUSIA DI KABUPATEN INDRAGIRI HULU - Fransinatra, Ziko; Gustika, Gita Sari; Ririen, Deci (JURNAL MANAJEMEN DAN BISNIS, 2019)
This research was conducted in Indragiri Hulu Regency. The data in this study are in the form of primary data obtained from questionnaires, observations and interviews. Secondary data obtained from non-formal education and training institutions are in the form of administrative documents. The population in this study were all education and training institutions (LPPNF) in Indragiri Hulu Regency. The sampling method utilizing total sampling Qualitative data processing uses descriptive statistics to systematically describe the facts and characteristics of objects appropriately. Correlation analysis uses SPSS 22.0 to determine whether there is a relationship (correlation) between variables and if there is a relationship, see the size of the relationship between variables. This study found the unique management of LPPNF management, which is management featuring one-man show. From the results of the analysis conducted, of course, inaccurate management will certainly have less than the maximum impact in achieving the goals of an organization. This is evidenced by the low number of human resources participating in training at LPPNF in Indragiri Hulu Regency. In the management of LPPNF, the objectives that have been well established should be regulated by these principles so that the objectives of the institution can be realized. The manager should run his LPPNF by following the good and correct management functions so that he can answer the need for human resources from the Business and Industry World in Indragiri Hulu Regency.   Keywords: LPPNF Management, Human Resources